2020
DOI: 10.21203/rs.3.rs-20531/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between adipokines and thyroid carcinoma: a meta-analysis of case-control studies

Abstract: Background: The incidence of thyroid carcinoma is on the rise all the world. Some studies have suggested that the change of adipokines can even induce thyroid carcinoma. However, other studies have come to the opposite conclusion. Therefore, we studied the relationship between adipokines and thyroid carcinoma. Methods: Databases—PubMed, Cochrane Library, SinoMed, CNKI, Wanfang, and clinical trial registries were searched. A meta-analysis was performed with sufficiently homogeneous studies. Twenty-nine articles… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…It has been found that many genes were related to the occurrence, development, and prognosis of THCA. Zhao et al performed a meta-analysis of case-control study and found a strong relationship between elevated concentrations of tumor necrosis factor-alpha (TNF-α) and THCA [4]. Lv et al identified 4 methylation-driven genes in THCA with independent prognostic value, which provided new insight into molecular mechanisms of THCA [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that many genes were related to the occurrence, development, and prognosis of THCA. Zhao et al performed a meta-analysis of case-control study and found a strong relationship between elevated concentrations of tumor necrosis factor-alpha (TNF-α) and THCA [4]. Lv et al identified 4 methylation-driven genes in THCA with independent prognostic value, which provided new insight into molecular mechanisms of THCA [5].…”
Section: Introductionmentioning
confidence: 99%